Development of Articulate Storyline-Based Learning Media in Differentiated Learning of Merdeka Curriculum in Elementary Schools - Sutisna, Atang; Heriyana, Tio; Susanti, Susi (ATTA`DIB, 2025)
Differentiated learning does not differentiate the learning treatment of students, but rather understands the strengths and weaknesses, as well as the learning needs of students according to their own learning styles. One of the efforts made to overcome this problem is to use articulate storyline learning media. The media products developed have complete features and are able to serve the diversity of student learning styles, namely having an attractive appearance, there are instructions for use, there are interactive learning materials (text, images, animations and videos), there is the development of student worksheets and has innovative learning evaluation features. The research method used is development research with the ADDIE model, the collection techniques used are observation, interviews, pre-test and post-test, paired sample t-test data analysis techniques. The research sample consisted of 31 fourth-grade students of Kaduagung State Elementary School. The results of the study of learning media based on Articulate Storyline in the material aspect obtained a very valid assessment of 92%, and the media aspect obtained a very valid assessment of 95%. The feasibility and practicality aspects were 90% by the supervising teacher and 87% by the students. The effectiveness test of the Paired Samples T Test obtained a value of (0.000 <0.05), which means there is a significant influence, so it is concluded that there is a significant influence of the use of articulate storyline-based learning media on differentiated merdeka curriculum learning at Kaduagung State Elementary School.